The Relationship Between Husband Support and Health Workers Support with Exclusive Breastfeeding Behavior in Sidotopo Village, Surabaya, Indonesia - Yurike Dian Pangesti1 , Shrimarti Rukmini Devy1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Exclusive breastfeeding is breast milk given to babies from birth to 6 months without added food or drinks except drugs for medical indications. Many factors can affect mothers in giving exclusive breastfeeding. The purpose of this study was to analyze the relationship between husband’s support and the support of health workers with exclusive breastfeeding. The research used observational analytic method with cross sectional research design. The sample in this study were 65 mothers who have baby aged 7-12 months in Sidotopo Surabaya. The research used simple random sampling technique with Chi-square test with 95% confidence level. The results showed there was no correlation between husband support (p = 0.426) and health workers support (p = 0.166) with the behavior of mothers in exclusive breastfeeding. The conclusion of the study is that there is no significant correaltion between husband support and health workers support with the behavior of mothers in exclusive breastfeeding. So it is necessary to increase counseling about the importance of exclusive breastfeeding, family planning counseling and lactation management.